Temporary VAT reduction during the lockdown - Marius Clemens; Werner Röger (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper evaluates the temporary VAT reduction introduced by the German government over the 3Q2020:4Q2020 as a controversial part of the COVID-19 stimulus package. Critics argue that VAT reductions are ineffective because of limited pass-through to consumer prices and during lockdown. Advocates emphasize positive effects on durable goods and stress that a VAT reduction can partly substitute for a limited monetary policy response under the zero lower bound (ZLB). Thus, the VAT policy experiment of a sizable two-quarter VAT reduction allows studying the effects and transmissions channels of VAT measures. We extend a dynamic stochastic equilibrium (DSGE) model to address a durable goods channel and a limited VAT pass-through and distinguish between sectors directly and indirectly affected by the lockdown. We trace lockdown and fiscal shocks and analyze the impact of the VAT reduction in conjunction with the lockdowns in 2020-2021 in Germany. We use nonlinear solution techniques to solve the model in the presence of a ZLB, forced savings and a partial lockdown constraint. Although the lockdown restriction reduces the effectiveness of a temporary VAT reduction, we find a short-term multiplier of 1.8. However, the cumulative multiplier reduces to below 1 over the medium term due to a shift in durable goods consumption toward 2020. Thus, the temporary VAT reduction is an effective instrument for short-term stabilization during the partial lockdown, but fiscal costs appear in the medium term.
Keywords: E62; E65; H12; 330; value added tax; fiscal policy; COVID-19; lockdown; multiplier; Germany